A Call to the Media to Change Reporting Practices for the Coverage of Mass Shootings - Jaclyn Schildkraut (Washington University Journal of Law & Policy, 2019)
This article considers how a more responsible form of media coverage of mass shootings could help to reduce the occurrence of these events. It begins by exploring evidence of a contagion effect, as well as the presence of copycat shootings, that result from the media coverage of these attacks. The article then assesses media coverage in light of the World Health Organization’s recommendations for coverage of a related phenomenon, suicide. The article argues for a shift of journalistic practices moving forward in an effort to help reduce the occurrence of mass shootings in the United States.
Keywords: mass shootings; media; gun violence; journalism; World Health Organization; coverage